Evaluating Gene Therapy and Immunotherapy for Cancer and Genetic Disorders - Ahmad Mukhlis Iliyas; Albert Elkington; Othman Abdul Wahab (Journal of Advances in Medicine and Pharmaceutical Sciences, 2023)
Gene therapy and immunotherapy have emerged as revolutionary treatments in medicine, offering hope for previously untreatable diseases, particularly cancer and genetic disorders. This study aims to analyze the progress and challenges in gene therapy and immunotherapy in the US healthcare system during 2022 and 2023, with a focus on their effectiveness, barriers to implementation, and regulatory hurdles. The methodology used in this study is a descriptive qualitative approach, using literature reviews, case study analysis, and data from clinical trials at institutions such as the NIH and Mayo Clinic. The findings highlight significant advances in gene therapies such as CRISPR for genetic disorders and cancer treatment, as well as the success of CAR-T cell therapy in hematologic cancers. However, both therapies face challenges, including high treatment costs, regulatory delays, and limited accessibility. Despite these challenges, this study highlights the promising future of these therapies, with advances in gene editing and immunotherapy expected to expand their applications. Future research should focus on long-term safety and efficacy, cost reduction strategies, and improved delivery systems for both therapies. Addressing these gaps will be critical to the widespread adoption of gene therapy and immunotherapy in clinical practice.